Biosynthesis of Phosphatidylglycerol in Isolated Mitochondria of Etiolated Mung Bean (Vigna radiata L.) Seedlings. - Griebau, R. (1994)
Phosphatidylglycerophosphate synthase (sn-glycerol-3-phosphate:CDP-diacylglycerol phosphatidyltransferase) and phosphatidylglycerophosphate phosphatase were characterized in mung bean (Vigna radiata L.) mitochondria. The synthase has a rather broad pH optimum between 7 and 9, whereas the phosphatase has one of about 7. Both enzymic activities are stimulated by Triton X-100 and require divalent cations but differ in their cation specificities. The synthase shows apparent Km values of 9 and 3 [mu]M for sn-glycerol-3-phosphate and CDP-diacylglycerol, respectively. Phosphatidylglycerophosphate, in contrast to lysophosphatidic and phosphatidic acid, is effectively dephosphorylated by the phosphatase, which exhibits an apparent Km value of 12 [mu]M for its substrate. Each enzyme shows higher activities with the dipalmitoyl species of its substrate than with the dioleoyl species. These substrate specificities of both enzymes are predominantly based on differences in apparent Vmax values.